Evolution of European carnivorous mammal assemblages through the Palaeogene. (18th February 2022) - Solé, Floréal; Fischer, Valentin; Le Verger, Kévin; Mennecart, Bastien; Speijer, Robert P; Peigné, Stéphane; Smith, Thierry
Abstract: The rise of Carnivora (Mammalia: Laurasiatheria) is an important evolutionary event that changed the structure of terrestrial ecosystems, starting at the dawn of the Eocene, 56 Mya. This radiation has been mainly analysed in North America, leaving the evolution of carnivoran diversity in other regions of the globe poorly known. To tackle this issue, we review the evolution of terrestrial carnivorous mammal diversity (Mesonychidae, Oxyaenidae, Hyaenodonta and Carnivoramorpha) in Europe. We reveal four episodes of intense faunal turnovers that helped establish the dominance of carnivoramorphans over their main competitors. We also identify two periods of general endemism. The remaining time intervals are characterized by dispersals of new taxa from North America, Asia and Africa. The European Palaeogene carnivorous mammal fauna appears to have been almost constantly in a transient state, strongly influenced by dispersals. Many of the bioevents we highlight for European carnivorous mammals are probably best seen as ecosystem-wide responses to environmental changes. In contrast to the North American record, European hyaenodonts remain more diverse than the carnivoramorphans for the entire Eocene. The replacement of hyaenodonts by carnivoramorphans as the most diverse and dominant predators only occurred after the 'Grande Coupure' at 33 Mya, about 16 Myr later than in North America.